Aplicação de técnicas de manejo localizado na cultura do arroz irrigado (Oryza sativa L.) - Durigon, Reges (2007)
While in the traditional agricultural management soil attributes variability used in the crop production has not been considered, the site-specific management aims to identify this variability. The main objective of the present work was to compare the site-specific management to the traditional management in the flooded rice crop describing the techniques and identifying economical and technicals factors that provide a viability analysis. For this reason, an experiment was carried out in a commercial flooded rice field with application of site-specific management techniques. The methodology consisted in the elaboration of soil attributes, management and yield maps and the correlations among these maps were used to elaborate maps of fertilizers application variable rate. The results showed variability in the flooded rice yield. The higgest positive correlations between the rice yield and soil attributes were verified for calcium and magnesium and the higgest negative correlations were for exchangeable aluminum and aluminum saturation. The application of lime at variable rate reduced the total amount lime used when compared to the application at the fixed rate and increased the profit margin yield, providing profitability of 71% with the operation. The results showed the technical and economical viability of use site-specific management techniques in the flooded rice crop.